If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2z + -7)(8 + z) = 0 Reorder the terms: (-7 + 2z)(8 + z) = 0 Multiply (-7 + 2z) * (8 + z) (-7(8 + z) + 2z * (8 + z)) = 0 ((8 * -7 + z * -7) + 2z * (8 + z)) = 0 ((-56 + -7z) + 2z * (8 + z)) = 0 (-56 + -7z + (8 * 2z + z * 2z)) = 0 (-56 + -7z + (16z + 2z2)) = 0 Combine like terms: -7z + 16z = 9z (-56 + 9z + 2z2) = 0 Solving -56 + 9z + 2z2 = 0 Solving for variable 'z'. Factor a trinomial. (-8 + -1z)(7 + -2z) = 0Subproblem 1
Set the factor '(-8 + -1z)' equal to zero and attempt to solve: Simplifying -8 + -1z = 0 Solving -8 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1z = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1z = 0 + 8 -1z = 0 + 8 Combine like terms: 0 + 8 = 8 -1z = 8 Divide each side by '-1'. z = -8 Simplifying z = -8Subproblem 2
Set the factor '(7 + -2z)' equal to zero and attempt to solve: Simplifying 7 + -2z = 0 Solving 7 + -2z = 0 Move all terms containing z to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2z = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2z = 0 + -7 -2z = 0 + -7 Combine like terms: 0 + -7 = -7 -2z = -7 Divide each side by '-2'. z = 3.5 Simplifying z = 3.5Solution
z = {-8, 3.5}
| (11/28)x=1 | | 13y-9+8=6 | | (3w-8)(2+w)=0 | | 3(2x-5)+2(4-x)= | | 6/7x=-14 | | x-40/x=3 | | 3+12x=93 | | x/1.2=5.3 | | 3(4x+3)+3(2x+5)+2=18x+26 | | 2(3x-6)=x+3 | | y=1/2x-12 | | 10y+2=6y+4 | | x^2-5-14=0 | | (x/6)-5=(x/2)-7 | | 3w(w)=108 | | 8y+10=6y+20 | | (3w)w=108 | | 44=50-5x+4x | | ax+b=c-a(x-b) | | -5x+12=16-3 | | 12x^3+48x-16= | | 2(i-3)=71-6 | | 11x-3x=17-20 | | f(x)=x^3+3x^2-24x-6 | | q*q+7*q+1=0 | | 2z=-2+10x | | q*q+7*p+1=0 | | 14=4x+6x+4+2 | | 5=40x+65y | | 5z^2+80=0 | | 7(X+7)=9X+9-2x+40 | | 4(8+2x)=8(4(8+2x)) |